Synthesis, characterization and dielectric properties of phosphazenes containing chalcones - Koran, Kenan; Ozen, Furkan; Torgut, Gulben; Pihtili, Gilzin; Cil, Erol; Gorgulu, A. Orhan; Arslan, Mustafa (PERGAMON-ELSEVIER SCIENCE LTD, 2014)
The new hexasubstitue-cyclophosphazene compounds containing chalcone derivatives (2-11) were obtained from the reactions of hexachlorocyclotriphosphazene (1) with several hydroxy chalcones in K2CO3/acetone system. All products were generally obtained in high yields. The structures of the compounds were defined by elemental analysis, FT-IR,H-1,C-13 and P-31 NMR spectroscopy. Dielectric measurements for phosphazenes containing chalcone compounds (5-8) were carried out by means of an impedance analyzer as a function of temperature and frequency. Dielectric properties of samples prepared in a plate form were measured at room temperature over the frequency range 50 Hz to 2 kHz and given as compared with each other. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: Hexachlorocyclotriphosphazene; Chalcone-phosphazenes; Dielectric properties; Trimer; Phoshorus; RAY CRYSTAL-STRUCTURE; ELECTRICAL-PROPERTIES; CYCLOPHOSPHAZENES; CONDUCTIVITY; AGENTS; DEPENDENCE; FREQUENCY; Chemistry; Crystallography